2011
DOI: 10.1007/s00431-010-1392-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurological complications of pandemic influenza A H1N1 2009 infection: European case series and review

Abstract: Neurological manifestations and outcomes of children with the 2009 H1N1 virus infection have been reported in three American series and from smaller cohorts and case reports worldwide. Of the 83 children admitted between April 2009 and March 2010 with H1N1 virus infection to a tertiary children's hospital in a European setting, five children aged between 2 and 10 years had neurological symptoms. Four patients had seizures and encephalopathy at presentation. One patient presented with ataxia; one developed neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 42 publications
(56 reference statements)
2
57
1
1
Order By: Relevance
“…We were able to calculate the proportion of neurologic complications in children hospitalized with laboratory-confirmed pandemic influenza in 2009 from 3 studies, 2 in the United States (5.9% and 7.5%) and 1 in the United Kingdom (6.0%). 15,19,29 The proportion of encephalopathy in children hospitalized with laboratory-confirmed pandemic influenza was 1.7% in another study. 12 The presenting symptoms, neurologic complications, CSF and neuroimaging findings, treatment, and outcome of the 87 children are summarized in table e-2.…”
Section: Participantsmentioning
confidence: 92%
“…We were able to calculate the proportion of neurologic complications in children hospitalized with laboratory-confirmed pandemic influenza in 2009 from 3 studies, 2 in the United States (5.9% and 7.5%) and 1 in the United Kingdom (6.0%). 15,19,29 The proportion of encephalopathy in children hospitalized with laboratory-confirmed pandemic influenza was 1.7% in another study. 12 The presenting symptoms, neurologic complications, CSF and neuroimaging findings, treatment, and outcome of the 87 children are summarized in table e-2.…”
Section: Participantsmentioning
confidence: 92%
“…The criteria stipulate laboratory-confirmed influenza A (H1N1) virus infection associated with seizures, encephalopathy, or encephalitis within 5 days of influenza-like illness (ILI), and without evidence of an alternative etiology [3]. The MRI findings in H1N1 encephalopathy include necrotising encephalopathy, posterior reversible encephalopathy and, as in our patient, callosal lesions typically located in the splenium [1,[5][6][7][8].…”
Section: Discussionmentioning
confidence: 96%
“…About 6% present with neurological features like seizures, encephalopathy, ataxia, movement disorders and neuropsychiatric manifestations [1]. There are only a few reports of H1N1 involving the nervous system in adults [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of IAE have generally failed to show direct viral infection of the CNS, suggesting an immune-mediated mechanism of tissue injury rather than direct viral toxicity. [1][2][3] Based on these observations and limited case reports of success of immunemodulating therapy in IAE, the patient was treated with a 5-day course of IV methylprednisolone 1000 mg daily as well as 1 mg/kg IV immunoglobulin (IVIg) given over 2 days. She demonstrated some purposeful movements on hospital day 9 and was extubated on hospital day 11.…”
Section: Sectionmentioning
confidence: 99%
“…3 The most common clinical features of ANE are generalized seizures and alterations of mental status including reduced level of consciousness, abnormal speech, and delirium. 1,3 Radiographic findings include symmetrically distributed lesions of the cerebral white matter and deep structures including the thalami and brainstem, with bilateral necrotic or hemorrhagic thalamic lesions being characteristic. 3,4 Multiple case series of IAE have demonstrated that CSF is generally noninflammatory, and virus can seldom be detected in CSF or in brain tissue.…”
Section: Sectionmentioning
confidence: 99%